A semantico-pragmatic analysis of amateur subtitling of swearwords in American crime drama movies into Arabic - Khalaf, Abed Shahooth (2016)
This study seeks to investigate the translation orientation of amateur subtitlers when rendering swearwords in American crime drama movies into Arabic. It focuses on a semantico-pragmatic analysis of such words in the selected movies and their subtitles in Arabic. This study also aims to identify the adopted translation strategies with emphasis on the effect of deletion on the conveyance of the intended meaning of swearwords to the target recipients and the causes of deletion. The study addresses four research questions: 1. To what extent have the semantic fields of swearwords in the movie dialogues been retained in the Arabic subtitles and what causes the resulting shifts? 2. To what extent have the pragmatic functions of swearwords in these movies been preserved in the Arabic subtitles? 3. What are the translation strategies adopted by amateur subtitlers to transfer swearwords in these movies into Arabic? 4. How does the deletion of swearwords in the Arabic subtitles affect the conveyance of their intended meanings and what are its causes? The data of the study comprise a corpus of the dialogue scripts of two American crime drama movies with high frequency of swearwords and their amateur subtitles in Arabic. The movie scripts and their subtitles formed a parallel corpus consisting of 73328 words. The content analysis method was used in extracting instances of swearwords using a concordancing software that searches for swearwords in context. The data were analyzed based on Allan and Burridge’s (2006) and Ljung’s (2011) models for semantic fields categorization and Wajnryb’s (2005) model for categorizing pragmatic functions. In addition, the identification of translation strategies was based on Vermeer’s (1978) Skopostheorie, and the types of meaning affected by the deletion of swearwords were determined using Leech’s classification of types of meaning (1981). The findings show a great variation in the semantic fields and incongruence of pragmatic functions between the swearwords in the source text compared to those in the subtitles, which resulted from the shift in the semantic fields of swearwords in the subtitles and inaccurate analysis by the subtitlers of the expressed pragmatic functions of such words in the movies. Besides, the subtitlers adopted certain target culture oriented translation strategies such as deletion, de-swearing, the use of deictic particles, ambiguity and euphemisms and other source text oriented strategies such as changing non-swearwords to swearwords, overtranslation, literal translation and functional equivalence. Being the most dominant adopted strategy, deletion of swearwords has affected the conveyance of the various types of associative meaning, which seem to relate to the expression of speakers’ inner feelings and their relationships with the addressees. The findings suggest that the translation orientation of amateur subtitlers has been influenced by the powerful sociocultural norms in the target culture, the subtitlers’ low linguistic/pragmatic competence and their lack of translation training and expertise. Accordingly, selfcensoring strategies as a means of conforming to the target recipients’ expectations were adopted, rendering their translation orientation a target culture oriented.